Epidemic trend, genetic characteristics, and transmission networks of HIV-1 among treatment-naive men who have sex with men in Hebei province, China - Lu, Xinli; Wang, Yingying; Ma, Lin; Liu, Meng; Li, Yan; An, Ning; Zhang, Xinyu; Tang, Xiangyun; Li, Qi (Frontiers in Microbiology, 2024)
Homosexual transmission has contributed greatly to the current HIV-1 epidemic in Hebei province, China. Dolutegravir (DTG) will be conditionally used as a component of free antiretroviral therapy (ART) according to manual for national free anti-AIDS treatment drugs (2023 edition) issued by China in June 2023. However, current genetic characteristics and pretreatment drug resistance (PDR) to proteinase inhibitors (PIs), reverse transcriptase inhibitors (RTs) and integrase strand transfer inhibitors (INSTIs) of HIV-1 in this population have remained unclear. Serial consecutive cross-sectional analyses for HIV-1 infection trend, genetic characteristics, PDR and molecular transmission networks were conducted from 2018 to 2022. All of participants were HIV-1-infected MSM newly diagnosed at the HIV surveillance points (HSPs) in Hebei, China. Evidence of PDR was confirmed using the world health organization (WHO) list for surveillance of drug resistance mutations. In this study, a total of 14 HIV-1 subtypes were circulating in the HSPs of Hebei province, China. CRF01_AE (51.9%, 350/675), CRF07_BC (30.4%, 205/675), B (6.2%, 42/675) and URFs (5.8%, 39/675) were the four most predominant subtypes among MSM.And, CRF07_BC (r>0) and URFs (r>0) indicated an increasing trend, respectively; however, CRF01_AE (r<0) showed a decline trend. The overall prevalence of HIV-1 PDR showed a substantial increase from 6.3% in 2018 to 7.9% in 2022. The prevalence of NNRTI-PDR was the highest (5.8%, 39/675), followed by INSTIs (2.4%, 16/675), NRTIs (0.6%, 4/675) and PIs (0.3%, 2/675). Furthermore, extensive HIV-1 strains bearing PDR were circulating in the MSM population via molecular transmission networks for major HIV-1 subtypes, especially CRF01_AE and CRF07_BC. Our findings reflect that HIV-1 epidemic in the MSM population is complex and severe in Hebei, China. Therefore, it is urgent for us to implement more effective intervention measures to limit the further dissemination of HIV-1, especially the spread of HIV-1 INSTI-PDR strains.